Enhancing Teachers’ Competence through Training on Android-Based Mathematics Learning Media: Peningkatan Kompetensi Guru melalui Pelatihan Media Pembelajaran Matematika Berbasis Android - Purnama, Nyoman; Putra, Made Adi Paramartha (Lembaga Riset dan Inovasi Masyarakat Madani, 2026)
The development of Android-based mathematics learning media using Unity 3D at SD Negeri 4 Padangkerta was conducted to address the limited use of interactive learning media in mathematics instruction. This community service activity aimed to enhance teachers’ competence in developing Android-based mathematics learning media through participatory training and hands-on practice. The program was implemented through stages of socialization, technical training on Unity 3D, prototype development assistance, and evaluation of training outcomes. The results indicate that 80% of participating teachers successfully produced Android-based learning media prototypes, accompanied by a 75% increase in teachers’ understanding of learning technology based on pretest and posttest evaluations. In addition, teachers demonstrated increased motivation and creativity in integrating digital technology into classroom learning. Overall, this activity contributes to strengthening teachers’ digital competence and improving the quality of mathematics learning using interactive and contextually relevant digital media.